PARENT INVOLVEMENT IN THE EDUCATION SYSTEM DURING THE CORONAVIRUS PANDEMIC: EFFECTS AND BARRIERS - Winkler, Ram (E-Journal VFU, 2025)
The coronavirus crisis caused significant changes in the global education system, with direct impact on about 1.6 billion students around the world, while presenting unique challenges to parents, students, and teachers. The rapid transition to online learning required adjustments on the part of the students and the teachers and also presented the parents with the need to fill new roles of educational accompaniment and emotional support, sometimes without prior preparation. The present research study examines the influences of the coronavirus lockdowns on the dynamics between parents and teaching workers, while focusing on the main challenges facing them. The research findings identified major barriers, such as personal, logistical, and financial difficulties, which limited the parents’ ability to cope with the new reality and provide optimal support to their children. The research conclusions emphasize the need to design an educational policy that supports parents, with the aim of reducing educational and social gaps and improving the children’s achievements during similar periods of crisis in the future.